The profile of the families who go through the decision-making process of donatiing their child’s organ - Peruchi, Fernanda (2007)
The aim of this study was to describe the profile of the families who go through the decision-making process of organ donation of their child. Data collection was made through the analysis of the handbooks from the Organ Procurement Organization (OPO) and statistically analyzed using the Qui-square test. The results show a predominance of nondonors (65%), greater frequency of deaths for violent causes (62%), predominance of adolescents (52%), average time of hospitalization of 7 days between the donors, and 4 days between the non-donors, and greater frequency of both parents approach (25%) during the interview with the OPO members. The limitations of this study included the absence of data in the handbooks regarding religion, family income, school level and parents’ occupation.